2020
DOI: 10.1016/j.ijid.2020.04.051
|View full text |Cite
|
Sign up to set email alerts
|

Statistical and network analysis of 1212 COVID-19 patients in Henan, China

Abstract: Background: COVID-19 is spreading quickly all over the world. Publicly released data for 1212 COVID-19 patients in Henan of China were analyzed in this paper. Methods: Various statistical and network analysis methods were employed. Results: We found that COVID-19 patients show gender (55% vs 45%) and age (81% aged between 21 and 60) preferences; possible causes were explored. The estimated average, mode and median incubation periods are 7.4, 4 and 7 days. Incubation periods of 92% of patients were no more than… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 25 publications
3
48
0
4
Order By: Relevance
“…Therefore, extra communication and health education may be needed to change the risk perception in rural areas and popular neighborhoods [22]. Brazilian students reported di culties to stay home, which may be related to a need to travel to their original homes in periods when schools and universities were closed [23] or could be related to differing social habits among this population. Encouragingly, respondents with underlying diseases followed the preventive measures well, which is important considering their higher risk for more severe disease.…”
Section: Adherence To the National Covid-19 Restrictionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, extra communication and health education may be needed to change the risk perception in rural areas and popular neighborhoods [22]. Brazilian students reported di culties to stay home, which may be related to a need to travel to their original homes in periods when schools and universities were closed [23] or could be related to differing social habits among this population. Encouragingly, respondents with underlying diseases followed the preventive measures well, which is important considering their higher risk for more severe disease.…”
Section: Adherence To the National Covid-19 Restrictionsmentioning
confidence: 99%
“…Our survey was also not able to reach vulnerable populations, such as the homeless, prisoners, older adults, migrants and people with mobility problems. Such populations may be at increased risk for COVID-19 infection and should be considered as priority key groups in the prevention and control of Covid-19 [23,34].…”
Section: Adherence To the National Covid-19 Restrictionsmentioning
confidence: 99%
“…Another recent analysis of detailed contact tracing data from Hunan, China, traced 80% of secondary cases back to 14% of infections [36]. Network analysis of COVID-19 patients in Henan, China, [14] revealed a non-uniform pattern of clustering (208/1105 patients in clusters) with a skewed distribution of patients in different cities. The Henan study also indicated a strong correlation of confirmed cases with travel to Wuhan (the epicentre of the pandemic), which corresponds to our observation that a fair proportion (17.44%) of the Karnataka patients had travelled to Delhi.…”
Section: Discussionmentioning
confidence: 99%
“…The work of Wang et al [17] applied statistical and network analysis on heterogeneous network containing patients and hospitals as nodes and relationships between relatives, friends or colleagues as edges. Network analysis provided important information about patients, hospitals and their relationships and it was able to provide a guidance for the distribution of epidemic prevention materials.…”
Section: Discussionmentioning
confidence: 99%